ICD exchange in the elderly. (14th October 2021) - Ritter, O; Pagonas, N; Eisert, M; Patschan, D; Nordbeck, P; Buschmann, I; Sasko, B; Andresen, H
Abstract: Background: ICD therapy in elderly patients is controversially discussed, since survival benefits might be attenuated by non-arrhythmic causes of death. Purpose: This study aimed to investigate the outcome of septua- and octogenarians after ICD generator exchange (GE). Methods: 506 patients undergoing elective GE were analysed to determine the incidence of ICD shocks and survival after GE. For further analysis, patients were divided according to age (70 – 79 or ≥80 years) and previous ICD therapy: patients that did not experience a shock and patients that received at least one shock from prior ICDs. Results: The effect of the ICD on all-cause mortality and arrhythmic death was determined for two groups (patients with 70 – 79 and ≥80 years). Comparing septua- with octogenarians, similar left ventricular ejection fraction (35.6±11.2% vs. 32.4±8.9%) and baseline prevalence of NYHA class 3 or 4 heart failure (17.1% vs. 14.7%) was found. Older patients were more likely to die of non-arrhythmic death (22% per year vs. 8% per year, p<0.001). We also investigated the necessity of ICD therapy dependent on whether ICD therapy occurred during the previous battery live. Septuagenarians and octogenarians with previous shocks had a higher incidence of further ICD therapy in the following battery life period (41% vs. 19%, p<0.001, and 22% vs. 17%, p<0.001). Conclusion: Decision making for ICD generator exchange among elderly patients should be considered carefully for an individual patient during clinical practice. Funding Acknowledgement: Type of funding sources: None.